Potential contribution of solar thermal power to electricity supply in Northern Nigeria - Ogunmodimu, Olumide Oluwaseun (Energy Research Centre, 2016)
Energy is an essential requirement for a reasonable socio economic development in a country; however, its provision depends on availability of energy sources and the require d investment. Nigeria possesses abundant deposits of energy sources ranging from fossil fuel to renewable energy sources. Over the years, the level of production of energy from these sources has been considerably low. The present level of electricity supply is short of demand and the supply is not reliable. As the country is experiencing rapid growth in population, adequate energy provision is necessary for corresponding level of production and development. The need for sustainable and renewable sources of energy has emerged globally owing to environmental issues associated with the use of conventional fuel. In order to consider the possibility of harnessing the solar energy resource in northern Nigeria, this study explores the potential contribution of the adoption of Concentrated Solar Power (CSP) technology to the energy system in the far northern States of Nigeria. These States are chosen because the region lies within a high sunshine belt and thus having a daily average DNI of 6.2 KWh/m2 / day and an annual average of 2320 KWh/m2/yr. The annual average DNI in the region is a bit higher than that of the Andasol CSP plant in Spain which is 2090 KWh/m2/yr. The thesis seeks to uncover the potential for CSP in Nigeria, and determine when the cost of energy from CSP will become competitive with the cost of energy from conventional power. Using three possible economic growth scenarios (reference (7%), high (10%) and optimistic (13%) economic growth scenarios) to model future energy demand and supply from CSP and conventional gas plant. The results obtained show possible competition from potential CSP plant in Nigeria depending on the international and domestic gas market. However, continuous payment of blanket subsidy on the domestic price of natural gas in Nigeria will adversely affect potential investment in CSP market in Nigeria.